PENGARUH HARGA JUAL DAN POTONGAN HARGA TERHADAP LABA PENJUALAN PADA PT. GIORDANO INDONESIA (TIMBERLAND) MEDAN - susanti, Eva; Hakim Siregar, Lukman (PT. ANAN PUBLISHER CENDEKIA, 2024)
This study aims to explain the impact of the sale price and price cuts on sales profits in Giordano Indonesia. Sampling techniques were used in this study of 60 respondents in a timberland store at PT. GIORDANO, Indonesia. The type of data that is collected is quantitative data (data expressed in the form of numbers), which is a number of answers from respondents. Besides, it also collects qualitative data, which is about the history of the company as well as the information needed to support this researcher. The test results of the first hypothesis show that the sale price is obtained: t_count > t_table = 4,285 > 1,671. Based on the result, H_0 is rejected and H_1 is accepted for the price influence variable. Thus, partially, the selling price has a significant positive influence on the sales profit at PT. GIORDANO INDONESIA. In the second hypothetical test, the price cut was t_count > t_tabel = 4,534 > 1.671. The result of the F test in this study is that the value of F_calculate > F_table = 35,192 > 3.16. Thus, it can be concluded that simultaneously, the sale price and the price reduction have a significant positive effect on the sales profit at PT. GIORDANO INDONESIA (timberland). Keywords: price of sale, price cut, profit of sale